Opioid prescription after common urgency general surgery procedures: An international perspective - N. Noppakunsomboon (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF Thailand| 2020 Objective: There are no guidelines for adequate postoperative pain control while lowering the risk of morphine overuse. To optimize the utilization of morphine derivatives, the proportions of patients and morphine amounts prescribed postoperatively have been studied worldwide. The present study reviewed the number of patients receiving morphine and the amounts administered at the Department of Acute Care Surgery. Materials and Methods: The use of postoperative oral morphine derivatives by patients undergoing common emergency general surgeries was retrospectively reviewed. Electronic data were collected of patients undergoing open appendectomy, laparoscopic appendectomy, laparoscopic cholecystectomy, open cholecystectomy, and open hernia surgery. The rates and amounts of the morphine derivatives prescribed during hospitalization and at discharge were analyzed. The amounts of the derivatives were converted to morphine milligram equivalents (MME). Results: Opioid derivatives were prescribed postoperatively for 22 patients (3.8%), with an average of 2.4 MME. Eighteen patients (3.1%) received intrahospital morphine derivatives (mean: 30 MME), while thirteen (2.2%) obtained them as a home medication (mean: 67 MME). The overall length of stay was 3.2 days (1 to 33), and the mean last pain score was 0.5 (0 to 7). A multiple logistic regression revealed that patients aged <60 years and with a BMI <25 had a higher proportion of morphine prescriptions. Conclusion: On case-by-case adjustments, a trivial amount of morphine derivatives was sufficiently prescribed to deal with postoperative pain following common general emergencies. The proportions of morphine prescriptions were higher among younger patients and those with average BMIs.